The Cultural Roots of Interventionism in the U.S - Martinot, Steve (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. Examination of the foreign military assaults conducted by the U.S., from Grenada in 1982 to Afghanistan in 2001, reveals the cultural roots of the nation's interventionism. The assaults violated a number of principles of international law and democracy and demonstrated a gap between policy and legitimacy, yet they all received overwhelming support at popular and institutional levels in America. Through messianic self-allegiance, paranoia, and violence, a legacy of white supremacy and white racialized identity manifests itself in U.S. interventionism.